Dual inclusion: gender and high abilities through arts education - Maldonado Esteras, Stella (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2023)
Girls and young women with high abilities represent a double paradigm of exclusion: on the one hand, they present cognitive and intellectual characteristics different from the average and, on the other hand, they are people who develop within a social and educational structure that is still very patriarchal. This makes it necessary to intervene so that they do not suffer exclusion, and their abilities and motivations are not cornered, hidden or made invisible. This has been repeated throughout history with the female gender, lacking sufficient references to validate their possibilities. This fact has also happened in the artistic field and, therefore, it is essential, first, to detect early the profiles; second, to change the paternalistic, social and family mentality with respect to high capacity in girls; and finally, to generate planning with a feminist perspective, working for a coeducation and equitable society that really attends and provides ways to develop talents. In this regard, the arts, within artistic educational programs, are a magnificent resource for promoting self-knowledge, the strengthening of identities, multidimensional expression, criticism, reflection and creation in freedom. Based on these premises, the project was designed and developed as a practical experimentation laboratory, aimed at children with high abilities and high motivation, which is presented here as a vehicle to work, from and with the arts, for an inclusive education of other socio-educational realities.